2016
DOI: 10.1111/cch.12411
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender differences in self‐control and its intergenerational transmission

Abstract: The roles of age, gender, parental self-control and SES varied in a dual-systems model of self-control: good self-control and poor control. Implications of these results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
2
24
0
1
Order By: Relevance
“…This corresponds to our previous knowledge that has surfaced from psychological research that shows a positive relationship between age and some of the achievement-related characteristics that are included in the BUSS scale-particularly grit, resilience, strength-use, self-control, well-being and mind-set. Indeed, previous research presents an age related shift in self-control [52,53]; grit [19,20]; resilience [25]; well-being [68,69] and mind-set [61]. It is believed that these characteristics increase as we age for numerous reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This corresponds to our previous knowledge that has surfaced from psychological research that shows a positive relationship between age and some of the achievement-related characteristics that are included in the BUSS scale-particularly grit, resilience, strength-use, self-control, well-being and mind-set. Indeed, previous research presents an age related shift in self-control [52,53]; grit [19,20]; resilience [25]; well-being [68,69] and mind-set [61]. It is believed that these characteristics increase as we age for numerous reasons.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that students' success and academic achievement are dependent on their ability to self-regulate, monitor their behaviour and control their actions [4]. For the most part research demonstrates that levels of self-control are similar among female and male university students [51]; however some research has also demonstrated that self-control is particularly male dominated [52]. While there are some discrepancies in the gender differences in self-control, research has demonstrated that university students are faced with several difficulties which test their self-control.…”
Section: Self-controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the previous study (Candeias et al, 2017;Angela Lee Duckworth & Seligman, 2006;Jo & Bouffard, 2014), male and female were differing in self-control, which female reported better than male. But this finding differs with Wang, Fan, Tao, and Gao (2017), which yield on male superior in Asian sample. This inconsistency perhaps linked with the cultural background lying on the sample.…”
Section: Discussionmentioning
confidence: 59%
“…In terms of age, it was found that the lower the age, the greater the negative impact of WhatsApp, the greater the negative consequences derived from the use of this tool, the greater the control of intimate relationships through this application was made and the greater the problematic use of WhatsApp was experienced, although due to the low correlation, the results need to be interpreted with caution. This could be because young people are more vulnerable to addiction in general and to problematic Internet use in particular, possibly because they are less self-controlled, less selfregulatory and more exposed to the network and new technologies (Jacobson, Bailin, Milanaik, Adesman, 2016;Wang, Fan, Tao & Gao, 2017). In addition, young people are less aware of the negative consequences of their actions, which would lead them to continue with addictive behaviours and experience an increasing negative impact.…”
Section: Discussionmentioning
confidence: 99%